1969
DOI: 10.1139/v69-687
|View full text |Cite
|
Sign up to set email alerts
|

Binuclear copper(II) complexes of the tetradentate ligand 1,4-di(2′-pyridyl)aminophthalazine: some novel five-coordinate derivatives

Abstract: Reaction of the title ligand (L) with copper salts leads to the formation of three principal series of compounds, LCu2X3(OH)•H2O (X = Cl, Br), LCu2(RCO2)3, and LCu2(RCO2)4, where RCO2 represents various aliphatic and aromatic carboxylate species. Magnetic data, electronic spectroscopic data both at room temperature and at −196 °C, infrared spectra, and microanalytical data are correlated to reveal that these complexes contain a binuclear copper-copper system in which the copper atoms are 5-coordinate and squar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
54
0

Year Published

1970
1970
2009
2009

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 74 publications
(55 citation statements)
references
References 9 publications
1
54
0
Order By: Relevance
“…Neutral ligand derivatives are confirmed for all the carboxylate complexes in the solid state, with the possible exception of VII, by the presence of at least one charge transfer band at 27000 cm-I or higher (13). Although compound VII has a solid state charge transfer band at 27500 cm-I, analytical and other data suggest an anionic derivative.…”
Section: Characterization Of the Complexesmentioning
confidence: 79%
See 4 more Smart Citations
“…Neutral ligand derivatives are confirmed for all the carboxylate complexes in the solid state, with the possible exception of VII, by the presence of at least one charge transfer band at 27000 cm-I or higher (13). Although compound VII has a solid state charge transfer band at 27500 cm-I, analytical and other data suggest an anionic derivative.…”
Section: Characterization Of the Complexesmentioning
confidence: 79%
“…Previous studies have shown that the presence of an infrared band above 1000 cm-I, associated with the ring breathing mode of the pyridine ring in PAP, indicates the coordination of this group to the metal centres (13). Absorptions in the range 1017-1025 cm-I (Table 2) for compounds V-IX indicate the involvement of the pyridine rings in coordination and suggest that PAP behaves as a tetradentate ligand.…”
Section: Characterization Of the Complexesmentioning
confidence: 81%
See 3 more Smart Citations